(untitled) (Revista Rupturas, 2018)
The article makes an approach to the gang concepts, youth squad and organized football bar. In the introduction, I expose how different social sectors, including academics, speak indifferently of one and another notion, not in a few cases, homologous them, thinking them as directly related practices. In a second section I will discuss a theoretical proposal: plural practices of youth, idea that I return from Zúñiga (2016) and Lahire (2005) to try to think about the set of youth situations related to these associations, which I will try to define in the third section thinking, in turn, of their objective differences and subjective similarities. In the fourth section I present two experiential cases that will support the previous section (distances and closeness between the referred youth practices), emphasizing the plurality of meanings of these dynamics. In the fifth and last section (conclusions) I will make a synthesis of the ideas outlined throughout the text.